1974
DOI: 10.1530/jrf.0.0370067
|View full text |Cite
|
Sign up to set email alerts
|

The Composition and Yield of Milk From Captive Red Deer (Cervus Elaphus L.)

Abstract: Summary. The gross anatomy of the mammary gland of the red deer is described. A total of 102 milk samples was obtained from six deer (four during a complete lactation). These contained an average of 21\m=.\1 % total solids (8\m=.\5% fat) in early lactation, rising to 27\m=.\1% (13\m=.\1% fat) in late lactation. Milk yieldswere measured by the calf-weighing technique. In well-fed hinds, peak yields of 1400 to 2000 g/day were reached early in lactation. One hind on a restricted food intake gave a maximum of 970 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
48
6

Year Published

1974
1974
2017
2017

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 103 publications
(73 citation statements)
references
References 12 publications
19
48
6
Order By: Relevance
“…Although we did not observe differences in suckling behaviour between light and dark hours in Experiment 1, in Experiment 2 it was noted that, even considering the fact that wild ungulates have to nurse very quickly, the time spent suckling seemed too short, especially when taking into account the fact that the daily milk intake is estimated to be up to approximately 2 litres (Arman et al 1974;Haigh & Hudson 1993;Landete-Castillejos et al 2000).…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…Although we did not observe differences in suckling behaviour between light and dark hours in Experiment 1, in Experiment 2 it was noted that, even considering the fact that wild ungulates have to nurse very quickly, the time spent suckling seemed too short, especially when taking into account the fact that the daily milk intake is estimated to be up to approximately 2 litres (Arman et al 1974;Haigh & Hudson 1993;Landete-Castillejos et al 2000).…”
Section: Discussionmentioning
confidence: 57%
“…The latter factor could be important in intensive deer farming since the identification of a given fawn's dam and its maternal ability (milking and nursing) would be difficult to measure. The fact that fawns seem to be fed by the herd rather than by their individual dams would also minimise the need to hand-rear orphaned or rejected fawns (Semiadi et al 1993a), a costly and time-consuming endeavour, in which a milk substitute is used (Arman et al 1974;Napolitano et al 1995).…”
Section: Discussionmentioning
confidence: 99%
“…while this investigation was in progress there appeared two large works on this theme (A r m a n et al, 1974, Briiggemann et al, 1973. One of them conducted on a subspecies occuring in Scotland (C.e.…”
Section: Introductionmentioning
confidence: 98%
“…The calving was assisted, but the calf died of an umbilical haemorrhage into the uterus. Arman et al (1974), and studies on calf growth will be reported elsewhere.…”
mentioning
confidence: 99%